Aspects of symmetry and topology in the charge density wave phase of 1T–TiSe2. (25th August 2021) - Huang, Shin-Ming; Xu, Su-Yang; Singh, Bahadur; Hsu, Ming-Chien; Hsu, Chuang-Han; Su, Chenliang; Bansil, Arun; Lin, Hsin
Abstract: The charge density wave (CDW) in 1 T –TiSe2 harbors a nontrivial symmetry configuration. It is important to understand this underlying symmetry both for gaining a handle on the mechanism of CDW formation and for probing the CDW experimentally. Here, based on first-principles computations within the framework of the density functional theory, we unravel the connection between the symmetries of the normal and CDW states and the electronic structure of 1 T –TiSe2 . Our analysis highlights the key role of irreducible representations of the electronic states and the occurrence of band gaps in the system in driving the CDW. By showing how symmetry-related topology can be obtained directly from the electronic structure, our study provides a practical pathway in search of topological CDW insulators.